Household green finances: demand in focus - Bethlendi, András; Póra, András (Public Finance Quarterly, 2021)
Based on a retail questionnaire survey conducted in the framework of the BME-MNB cooperation we aimed to answer to the following main research questions: 1) how the households’ environmental and financial knowledge and attitudes are related to the demand for green financial products, 2) how significant (price) support shall be used to channel Hungarian consumers towards more sustainable financial products. In addition, we aimed to explore the households’ green and financial knowledge and attitudes. During the study, aggregate indices and indicators were created to study the main issues, which formed the basis of the analysis. The Hungarian population generally has a positive attitude towards environmental protection. Respondents tend to underestimate their green knowledge and their financial knowledge prudence. Education and financial literacy are also the most important in terms of financial and green knowledge and attitudes. Concerning personal green attitude, it can be said that the pragmatism provided by the financial possibilities is decisive in everyday life. Demand for financial products is most affected by pricing, green and financial knowledge indices, and age (demography). Based on the results, only a significant price subsidy could steer domestic consumers towards more sustainable financial products.